Faktor-Faktor Stres Kerja dan Keseimbangan Kehidupan Kerja Terhadap Turnover Intention Pada Karyawan Hotel Claro Makassar - Muhammad Syafii A. Basalamah; Suzanna Rosario Sinaga; Mursalim Mursalim (Departement of Mathematics Education, 2023)
This research was located at the Claro Makassar Hotel. The purpose of this study was to determine the effect of work stress and work-life balance on employee turnover intention. This type of research is quantitative with the aim of finding answers to research questions based on actual circumstances. This study used a sample of 81 respondents. This sampling using purposive sampling. The test equipment used was the research instrument test and path anaylisis with the SPSS version 26.0. The result of this study is that the variable of work stress has an effect on employee turnover intention. The work-life balance variable effects the turnover intention of employee. The effect of work stress on turnover intention is positive and significant. The influence of work-life balance on turnover intention is negative and significant